Effect of extrusion cooking of white yam (Dioscorea rotundata) and bambara-nut(Vigna subterranean) Blend on some selected extrudate parameters (2011)
The effect of thermo-extrusion processing of white yam (Dioscorea rotundata) and bambara nut (Vigna subterranean) on some selected extrudate parameters of residence time, throughput and moisture content were investigated in this study. Both yam and bambara nut were processed into meals of750 um and 500 um respectively. Extrusion was carried out following a three variable response surface methodology using a Box Behnken design. Blend of yam meal and Bambara nut meal at ratio 80:20 respectively was conditioned into 12.5, 15.0 and 17.5% moisture content (dry basis) and allowed to equilibrate for 4 h. Extrusion was carried out on a single screw extruder at 50, 60 and 70 rpm screw speed and l30 ·C, 140·C and 150·C barrel temperatures. The study revealed that the extrusion time varied between 13.1 and 29.7 see, throughput variedfrom 13.3 to 34.4 kg/h and product moisture rangedfrom 11.l to 16.8% dry basis). All investigated extrudate parameters were significantly affected ip < 0.05) by the process variables of screw speed, barrel temperature and feed moisture content, and their interactions. The results were indicative that the second order polynomial